Electrolyzed Sulfuric Acid Application in Semiconductor Cleaning Processes: An Advanced Substitution of SPM Cleaning. (26th April 2017) - Ahn, Jin-hyun; Kim, Pyung Dae; Hwang, Seong Cheol; Seo, Jinyoung; Lee, Sungjin; Ogawa, Yuichi; Ida, Junichi; Sasaki, Yuya; Nagai, Tatsuo; Otsu, Toru
Abstract : For SPM(Sulfuric acid Peroxide Mixture) cleaning, a widely used method in semiconductor process, the density of peroxide is the main factor for metal and polymer removal. As the technology node shrinks, the need for both better polymer removal performance and less for metal removal is required. However, with only one factor is available for SPM cleaning. In this paper, by electrolysis of sulfuric acid, we utilized peroxydisulfate(S2 O8 2- ) instead of peroxide in semiconductor processes, resulting in better residue removal with same amount of metal removal.